100 Years of Fashion - Blackman, Cally (London : Laurence King Publishing, 2012)
This text documents in pictures the most exciting and diverse period in fashion: from 1900 to today, covering high society, uniforms, sportswear, streetwear and couture. It will appeal to everyone with an interest in fashion as well as students.
1901-1959. High Society -- Bohemian -- Uniformity -- Amazons -- Couturiere -- Star -- Patriot -- New looks -- 1960. Youthquake -- Denim and Sport -- Outsider -- Designer: Minimal -- Designer: Colour -- Designer: Concept -- Designer: History and Heritage -- Fashion and fame.
Includes index.
Keywords: Fashion -- History -- 20th century -- Pictorial works; Fashion -- History -- 21st century -- Pictorial works; Clothing trade